Gulags, Crime, and Elite Violence: Origins and Consequences of the Russian Mafia - Jakub Lonsky (Global Labor Organization (GLO), 2020)
This paper studies the origins and consequences of the Russian mafia (vory-v-zakone). Using a unique web scraped dataset containing detailed biographies of more than 5,000 mafia leaders, I first show that the Russian mafia originated in the Soviet Gulag archipelago, and could be found near the gulags' initial locations in mid-1990s Russia, some three decades after the camps were officially closed down. Then, using an instrumental variable approach that exploits the proximity of the Russian mafia to the gulags, I show that Russian communities with mafia presence in the mid-1990s experienced a dramatic rise in crime driven by elite violence which erupted shortly after the collapse of the Soviet Union in 1991. The violence – initially confined to the criminal underworld – eventually spilled over, leading to indiscriminate attacks against local businessmen, managers of state-owned enterprises, judges, and members of the state security apparatus. However, there was no increase in politically-motivated violence, suggesting a widespread collusion between the mafia and local politicians in the early post-Soviet Russia.
Keywords: K42; N40; P16; P37; 330; Russian mafia; Gulag; Post-socialist transition; Crime; Elite violence